Pengaruh Dana Pihak Ketiga dan Pembiayaan Bermasalah Terhadap Pembiayaan Mudharabah - Raplih, Muhamad; Budiman, Septian Arief (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This research aims to analyze the influence of Third Party Funds and Problematic Financing on Tax Aggressiveness. This research was conducted by analyzing company financial reports at Indonesian Sharia Commercial Banks registered with the OJK for 2019-2023. The sample used in this research was 8 Indonesian Sharia Commercial Bank companies registered with the OJK in 2018-2022 using a purposive sampling technique. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The analytical method used is panel data regression analysis. Analysis of research results using the Eviews 9 program. The results of this research show that partially third party funds have an effect on mudharabah financing and problematic financing has an effect on mudharabah financing. Simultaneously, third party funds and problematic financing influence mudharabah financing.